Организация режима работы и обслуживания оборудования на металлургическом предприятии - Гриднева, Г. И.; Косарева, И. Н.; Кобзева, А. Г. (НТУ "ХПИ", 2014)
Целью данной работы является оценка расходов, связанных с простоями оборудования из-за отказов роликов, и поиск путей снижения этих расходов. В прокатном производстве применяются рабочие и транспортные рольганги. Рольганги работают в весьма тяжелых условиях: их ролики подвергаются ударам и поэтому износ роликов является причиной наиболее частых остановок этих рольгангов. Использование имитационного моделирования позволяет сократить сроки и затраты на ремонт роликов.

The aim of this work is to estimate the costs associated with equipment downtime due to failures of the rollers, and finding ways to reduce these costs. This article investigated the operation and maintenance of equipment at a metallurgical plant. In the rolling operations are working and the transport roller. Roller conveyors are working in very difficult conditions: their videos are being hit hard and therefore the wear of the rollers is the cause of the most frequent stops these roller conveyors. The lifetime of each clip and the time of its failure are random variables and to calculate using simulation and the Monte Carlo method. To conduct simulation used data on the distribution of lifetimes of rollers, derived from the aggregate log. The use of simulation allows to reduce the time and cost of repair of the rollers.
Organization of operation and maintenance of equipment in metallurgical plant
Keywords: транспортировка; рольганги; простои оборудования; прокатное производство; срок службы; затраты; метод Монте-Карло; roller conveyors; equipment downtime; costs; service life; random variable; Monte Carlo method